Microcalorimetry in a Historical Aspect, State of Art and Prospects: Part 1. - Mykytiuk, P.D.; Mykytiuk, O.Yu.; Mykytiuk, O.P. (Journal of Thermoelectricity, 2025)
This article scrutinizes the development of calorimetry since the 17th century on. It shows how calorimetry methods changed depending on the acquisition of new knowledge about the nature of heat and thermal processes. The influence of the industrial revolution on the development of calorimetric methods is reflected. The achievements of microcalorimetry in the 20th century and at this stage are demonstrated. The main applied directions of practical use of microcalorimeters are shown. A prospect of possible promising achievements in the field of microcalorimeters and an analysis of the ways to achieve them is made.